2012
DOI: 10.1111/phpp.12001
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection counseling of non‐white ethno‐racial groups: a survey of the practice of expert dermatologists

Abstract: The morbidity of skin cancer in non-white, ethno-racial populations is well established, yet no specific guidelines exist addressing the manner in which this population should be counseled on photoexposure. We conducted a 20-item survey to assess the behavior of specialized dermatologists when providing photoprotection recommendations to non-white, ethno-racial patients as well as the perceived relevance of counseling for this group. Our study demonstrated that key opinion leaders within the fields of photoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…While the findings discussed in this review article are not generalizable to all SOC populations and geographic regions, they highlight the unique considerations and challenges to photoprotection that need to be further examined. As we learn more, counseling remains the critical piece in SOC patients [ 146 , 147 ] and this will only become more important as the relative sizes of SOC populations continue to increase over the next decades in the US [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the findings discussed in this review article are not generalizable to all SOC populations and geographic regions, they highlight the unique considerations and challenges to photoprotection that need to be further examined. As we learn more, counseling remains the critical piece in SOC patients [ 146 , 147 ] and this will only become more important as the relative sizes of SOC populations continue to increase over the next decades in the US [ 148 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 6 | PREVENTION PRACTICES In another study of 50 dermatologists, sun protection counseling was not routinely given to PAD despite the thinking that sun protection is important in PAD. 52 It is believed in PAD that, the dark skin tone is enough protection. Agbai et al in a review article on skin cancer and photoprotection in people of color, concluded that, there was a low use of sunscreen in PADs.…”
Section: Socioeconomic Status Awareness and Perception Of Risk Of mentioning
confidence: 99%
“…In another study of 50 dermatologists, sun protection counseling was not routinely given to PAD despite the thinking that sun protection is important in PAD 52 . It is believed in PAD that, the dark skin tone is enough protection.…”
Section: Prevention Practicesmentioning
confidence: 99%
“…Black individuals often perceive themselves as having a lower risk of melanoma, possibly due to the comparatively lower incidence rates when compared to White individuals. Unfortunately, these misconceptions can result in a reduced frequency of skin self-examinations [8][9][10][11]. Furthermore, there is a notable lack of melanoma awareness and risk perception, coupled with a lack of educational initiatives specifically tailored to darker skin tones, both within the general public and among healthcare providers.…”
Section: Introductionmentioning
confidence: 99%